Complete mitochondrial genome of the giant ramshorn snail Marisa cornuarietis (Gastropoda: Ampullariidae). (3rd May 2016) - Wang, Mingling; Qiu, Jian-Wen
Abstract: We report the complete mitochondrial genome (mitogenome) of the giant ramshorn snail Marisa cornuarietis, a biocontrol agent of freshwater weeds and snail vectors of schistosomes. The mitogenome is 15, 923 bp in length, encoding 13 protein-coding genes, 22 transfer RNAs and 2 ribosomal RNAs. The mitogenome is A+T biased (70.0%), with 28.9% A, 41.1% T, 16.7% G, and 13.3% C. A comparison with Pomacea canaliculata, the other member in the same family (Ampullariidae) with a sequenced mitogenome, shows that the two species have an identical gene order, but their intergenic regions vary substantially in sequence length. The mitogenome data can be used to understand the population genetics of M. cornuarietis, and resolve the phylogenetic relationship of various genera in Ampullariidae.